Tuintaferelen '88. (Kalmthout : Tuintaferelen '88 v.z.w., 1988)
Aerts, Barthold ; Aguirre y Otegui, Philip ; Baekelmans, Guy ; Boons, Anna ; Coppens, Mariette ; Cornelissen, Remi ; De Bie, Annie ; De Kort, Jetje ; Dupont, Veerle ; Goossens, Walter ; Lauwers, Laurent ; Maeyens, Dirk ; Mazy, Marcel ; Pacquee, Ria ; Peeters, Dré ; Roelandt, Hugo ; Schaetling, Chris ; Thys, Raf ; Verhelst, Eric ; Zaman, André ; etc.
Tuintaferelen '88, Kalmthout - Kapellen, 11.9. - 23.10.1988
boek